Losing the Battle: Questioning Postcolonial Aesthetic Hegemony Represented in Illustration Pictures at Taman Pintar Yogyakarta - Kasiyan Kasiyan (Journal of Urban Society's Arts, 2019)
This article describes the postcolonial aesthetic hegemony which is represented in illustration pictures in one of the educational tourist attractions in Yogyakarta, namely Taman Pintar, along with its causes. This study used a hermeneutic approach, with the main instrument is the researcher himself as a human instrument. Meanwhile, the analysis technique used is descriptive qualitative. The results of the analysis revealed some points. Firstly, the form of postcolonial aesthetic hegemony in illustration pictures of Taman Pintar, is manifested by the use of pictures of the inventors of modern science. All of the inventors came from the West, and none of them came from the East. This has lead to the construction of discourse with Western bias. This phenomenon is a kind of losing the battle in the cultural constellation that is not supposed to be transformed and internalized to young generations that are going to be the next generations of this country in the future. Secondly, this phenomenon of Western hegemony is caused mainly by the existence of the strong burden of Western post-colonialism syndrome faced by this nation, Indonesia.